Incremental prognostic value of cardiopulmonary exercise testing and resting haemodynamics in pulmonary arterial hypertension - Wensel, Roland; Francis, Darrel P.; Meyer, Franz Joachim; Opitz, Christian F.; Bruch, Leonhard; Halank, Michael; Winkler, Jörg; Seyfarth, Hans-Jürgen; Gläser, Sven; Blumberg, Friedrich; Obst, Anne; Dandel, Michael; et al. (International journal of cardiology, 2013)
Background - Pulmonary arterial hypertension (PAH) is a fatal disease despite recent treatment advances. Individual risk stratification is important. Exercise capacity and invasive haemodynamic data are both relevant, but data on the combined prognostic power are lacking. - Methods - 226 consecutive patients with idiopathic or familial PAH were included at seven specialised tertiary centres. All patients underwent right heart catheterization and cardiopulmonary exercise testing (CPET). - Results - During follow-up (1508±1070days) 72 patients died and 30 underwent transplantation. On multivariate analysis percentage of predicted peak oxygen uptake (%predicted peak VO2 [risk ratio 0.95]), pulmonary vascular resistance (PVR [1.105,]) and increase in heart rate during exercise (ΔHR [0.974]) were independent prognostic predictors (all p<0.0001). Peak VO2 allowed for risk stratification with a survival of 100, 92.9, 87.4 and 69.6% at 1year and 97.7, 63.2, 41 and 23% at 5years for the 4th, 3rd, 2nd and 1st quartiles, respectively. Dichotomizing by median peak VO2 and intra-group median PVR showed a worse 1-year survival for patients with low peak VO2/higher PVR compared to patients with low peak VO2/low PVR, high peak VO2/high PVR and high peak VO2/low PVR (65 vs. 93, 93, 100%, p<0.001). At 10years survival was different for all 4 subgroups (19 vs. 25 vs. 48 vs. 75%, adjusted p<0.05). - Conclusions - Peak VO2, PVR and ΔHR independently predict prognosis in patients with PAH. Low peak VO2, high PVR and low ΔHR refer to poor prognosis. Combined use of peak VO2 and PVR provides accurate risk stratification underlining the complementary prognostic information from cardiopulmonary exercise testing and resting invasive haemodynamic data.
Available online 10 April 2012
Gesehen am 04.11.2021